Analysis of the Interaction and Contribution of Islamic Human Development Index (IHDI) and Total Islamic Banking Assets in Indonesia's Economic Growth - Muhammad Agung Nugraha; Imsar Imsar; Aqwa Naser Daulay (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the effect of Islamic Human Development Index (IHDI) and total Islamic banking assets (APS) on Indonesia's economic growth using Vector Error Correction Model (VECM) analysis. This type of research data uses time series data for the period 2010-2023. This study uses a quantitative approach to Vector Error Correction Model (VECM) analysis. This research is short and long term regression, as well as the Granger causality test to evaluate the relationship between variables. The population in this study reports IHDI, Total Islamic Banking Assets, and economic growth in the period 2010-2023 so that the sample of this study amounted to 168 months analyzed using EViews software. The results showed that in the short term, IHDI and APS have a positive and significant influence on economic growth. However, in the long run, although the effect is positive, the relationship is not significant. The Granger causality test reveals that the causality relationship is one-way, where APS affects IHDI and APS affects PE. This confirms the role of APS in improving Islamic value-based quality of life and supporting economic growth. In contrast, the causal relationship between IHDI and PE was not shown to be significant in either direction. This study recommends increasing Islamic financial literacy, strengthening regulations that support APS growth, and integrating IHDI into development policies to create inclusive and sustainable economic growth. These findings are relevant in developing development strategies based on Islamic values for Indonesian society.